2005
DOI: 10.1002/pri.14
|View full text |Cite
|
Sign up to set email alerts
|

Case report: inspiratory muscle training in chronic critically ill patients — A report of two cases

Abstract: These positive results indicate further research is needed to investigate the effect of inspiratory muscle training on respiratory function, exercise tolerance and functional performance, for the possible inclusion of inspiratory muscle training into the physiotherapy management of patients following prolonged mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Chang et al33 observed a post-weaning reduction in the inspiratory muscle strength of patients who had undergone a lengthy period of mechanical ventilation. These results are in agreement with those for the control group, as shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al33 observed a post-weaning reduction in the inspiratory muscle strength of patients who had undergone a lengthy period of mechanical ventilation. These results are in agreement with those for the control group, as shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,8 Inspiratory muscle strength training (IMST) has shown promise to counteract inspira-tory muscle weakness. 9,10 A controlled clinical trial from our laboratory demonstrated that IMST increased static maximum inspiratory pressure (P Imax ) and facilitated ventilator weaning in MV-dependent adults. 11 A recent systematic review of IMST also found that higher-intensity training with pressure-threshold devices conferred greater strengthening benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy people and in people with chronic obstructive pulmonary disease, IMT increases respiratory muscle strength and endurance [19-22]. The effectiveness of IMT in increasing inspiratory muscle strength and endurance in ventilated patients (to potentially reduce weaning duration) has not yet been established.…”
Section: Introductionmentioning
confidence: 99%